COVID-19, Racism and Politicization Media in the Midst of a Pandemic. - Seneviratne, Kalinga (Cambridge Scholars Publisher, 2021)
This book explores the global response to the COVID-19 pandemic, and the role of national and international media and governments in the initial coverage of the developing crisis. With specific chapters written mostly by scholars based in these countries, it examines how the media in India, China, Sri Lanka, Philippines, Taiwan, Bangladesh, New Zealand and the USA responded to this pandemic. The volume particularly addresses their role in both countering and spreading misinformation and in the politicization of the health crisis. The chapters highlight various issues specific to individual cou.